La datation dendrochronologique du coffrage de fondation d’une pile du pont-siphon de l’Yzeron à Beaunant (Sainte-Foy-lès-Lyon, Métropole de Lyon) - François Blondel; David Baldassari (Gallia)
The Yzeron siphon bridge at Beaunant (Sainte-Foy-lès-Lyon) was 290 m long at the deck and 18 m high in its central part. It had 30 arches supported by 29 piles. The bridge supported the penstocks of a siphon nearly 2,260 m long, allowing the Gier aqueduct to cross the Yzeron valley, which at this point is 1,500 m wide and 125 m deep. Pile 18 –examined during a preventive archaeology excavation carried out in 2018 in the river bed– had a foundation mass that required the use of wooden formwork for its realisation in masonry.This formwork consists of fir planks laid on edge and roughly nailed to squared fir posts. The formwork is attested at least on the southern and eastern sides of the pile. Because the state of preservation of the formwork timbers was uneven, only about twenty samples could be taken, in some cases several from the same timbers. In the end, at least eight boards and six posts were removed, two of which were of circular cross-section found at the front of the formwork.Among the 14 timbers measured, not all show the same number of rings because of the cutting method and the age of the fir trees. The number of rings measured thus varies from 16 to 62. The posts most often have their first growth ring preserved (pith) and sometimes their last ring at the time of collection (cambium). However, they correspond to the shortest growth series, from 16 to 40 rings. The preparation of the boards, cut on a slab by sawing, leads to a loss of material and therefore of rings, that varies in scale according to their location in the tree. For these timbers, the pith and cambium are rarely preserved. However, they correspond to the longest series, with between 30 and 62 rings. The similarity of some of the growth curves indicates that some of the timbers are from the same fir tree. This is the case for at least three of the eight boards.These different series were synchronised with each other. Posts with few rings were discarded because of the absence of overlap with the longer series and will remain undated, except for one post with 40 rings. An average of 82 years was generated from nine individual samples (one post and the eight boards).The comparison of this average with the dated benchmarks give a date of 110 CE. This dating is supported by the different correlation values obtained and the replications for the same dating. The most significant correlation values concern the Auvergne-Limagne benchmarks, but also those of numerous sites in eastern France.These results also make it possible to extend investigation to the provenance of the fir trees used to make the formwork. The growth area of fir trees varies in its distance from the Beaunant site, with a spontaneous distribution from the montane level between 400 to 1800 m in altitude. The formwork timber necessarily requires a supply of raw timber, or partially processed wood in the case of the boards. Several supply areas can be envisaged at varying distances: the Pilat and Ardèche mountains to the south/south-west, the Lyonnais, Forez and Livradois-Forez mountains to the west and the southern part of the Jura massif as well as the northern Pre-Alps to the east. The assumed distances range from around 20 to 65 km.Comparing the correlation results between the different dated sites over a large area, the highest values are concentrated only on the ancient site of Ambert-La Masse (Puy-de-Dôme). This artisanal site on the banks of the Dore is also the closest geographically to Beaunant, had a distance of 80 km. This high correlation value (Student’s t = 5.25 and coefficient (r) = 0.61) most likely suggests a supply of fir from the west. This limits the forests exploited to the Pilat massif, Monts Lyonnais or the Forez foothills. A comparison of these results with the route of the Gier aqueduct, which originated at the foot of the Pilat massif, provides clues to a probable source in this sector. Indeed, the dendroprovenance approach indicates a common climatic signal between the Beaunant and Ambert-La Masse sites. It is therefore likely that the water comes from this part of Forez, the Pilat massif or Monts Lyonnais. The location of the aqueduct’s feeder catchment and its route, on the edge of the fir zone, suggests several terroirs likely to provide timber for its construction, both for scaffolding and for foundation formwork such as that discovered at Pile 18. It is therefore very likely that the need for timber is part of a windfall opportunity generated by the work on the Gier aqueduct itself and by tree felling in the vicinity of its route.